Mortality, morbidity and health selection among metal workers - Koskela, Riitta-Sisko (Scandinavian Journal of Work, Environment & Health, 1997)
Workers are selected into and out of physically demanding jobs with regard to their health. The study of occupational mortality and morbidity is hampered by this selection. Furthermore, social selection and rapid turnover are involved in health selection. Because different stages of disease form only one continuum (dissatisfaction - death), the correct interpretation of the results also requires measures softer than mortality. Earlier studies have concluded that soft and hard measures of health follow one another as explanations for the termination-of-employment rate. The aim of this study was to determine which age and exposure categories are the most prone to health selection. Mortality and morbidity were studied on three different exposure levels defined primarily according to the physical demands of the work: heavy level (iron foundries); medium level (manufacture of metal products); and light level (manufacture of electrical devices). The population comprised 15 714 men hired in 1950-1976 to work in the three branches of the metal industry. Another cohort, a cross-sectional one, of 1292 workers (who had been hired earlier and were still working in 1950) in the three industrial branches was used to clarify selection due to disability and mortality. Data for the mortality and disability analyses were obtained from national death and disability registers. The periods of follow-up were 1950-78 and 1950-87. A questionnaire on occupational history, morbidity, and the causes of turnover was sent to 400 current and 600 former workers from each industrial branch. A questionnaire concerning occupational history was also sent to the nearest relatives of a total of 450 decidents. The occupational histories of the current and former workers were compared for changes in the exposure level throughout their complete occupational histories. The occupations during the workers' lifetimes were also classified into three exposure levels on the basis of physical demands (heavy, medium, and light). The three exposure levels showed different patterns of change according to age throughout the workers' complete occupational histories. Selection into and out of jobs within and between different exposure levels appeared to be a continuous process, a chain of selection. This conclusion was ascertained when the complete occupational histories were analyzed according to the exposure levels (heavy, medium, light) of the occupations from which the workers came and to which they transferred. The foundry workers entered the industry from either heavy or medium-level occupations, and most of them sought lighter work in medium-level occupations. The metal product workers either began their work lives within the metal product industry or they transferred to it from work that entailed the same exposure level. After leaving a job, the metal product workers generally moved to medium (ie, the same level) or light occupations. The electrical workers switched from medium-level work, or they began their worklives within that industrial branch. When they left a job, they chose medium or light work in the metal industry. Due to the chain of selection from one exposure level to another, the mortality and morbidity rates for a certain exposure level can be underestimated or overestimated if complete occupational histories are not available. The selection process was different for different diseases and was manifested as different stages of disease. Ache or pain in the musculoskeletal system within the last 12 months was more frequent among the foundry and metal product workers than among the electrical workers. Both the currently employed and former foundry workers had significantly more earlier-diagnosed musculoskeletal diseases than the electrical workers. The younger age classes of foundry workers (